Socioeconomic Position and Type 2 Diabetes: The Mediating Role of Psychosocial Work Environment- the Maastricht Study - Bengisu Sezer; Bengisu Sezer; Annemarie Koster; Annemarie Koster; Jeroen Albers; Jeroen Albers; Rachelle Meisters; Rachelle Meisters; Miranda Schram; Miranda Schram; Miranda Schram; Miranda Schram; et al. (Frontiers Media S.A., 2023)
Objective: We examined the association between low socioeconomic position (SEP) and Type 2 Diabetes Mellitus (T2DM), and the mediating role of psychosocial work environment by using counterfactual mediation analysis.Methods: Data from 8,090 participants of The Maastricht Study were analysed. SEP indicators (education, income, occupation), self-reported psychosocial work stressors, (pre)diabetes by oral glucose tolerance test were measured at baseline. Incident T2DM was self-reported per annum up to 9 years. Cox regression and causal mediation analyses were performed.Results: 2.8% (N = 172) of the participants without T2DM at baseline reported incident T2DM. People with lower SEP more often had prevalent T2DM (e.g., education OR = 2.49, 95% CI: 2.16-2.87) and incident T2DM (e.g., education HR = 2.21, 95% CI: 1.53-3.20) than higher SEP. Low job control was associated with prevalent T2DM (OR = 1.44 95% CI: 1.25-1.67). Job control partially explained the association between income and prevalent T2DM (7.23%). Job demand suppressed the associations of education and occupation with prevalent T2DM. The mediation models with incident T2DM and social support were not significant.Conclusion: Socioeconomic inequalities in T2DM were present, but only a small part of it was explained by the psychosocial work environment.